Costal BCG osteomyelitis developing 1 year after BCG vaccination. Issue 5 (18th October 2013) - Oyachi, Noboru; Obana, Kazuko; Suzuki, Takeyuki; Kimura, Shuri; Chino, Kozo; Oyama, Toshio; Takano, Kunio
Abstract Reported here is the case of a 15‐month‐old boy with costal osteomyelitis due to the bacillus Calmette–Guérin (BCG) vaccine against tuberculosis. Mild complications of this vaccine, such as localized abscess and regional lymphadenitis, are occasionally recognized, but its association with osteomyelitis is extremely rare.